2020
DOI: 10.18203/2349-3291.ijcp20201133
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of serum leptin levels with clinical and biochemical parameters in obese children

Abstract: Background: Leptin plays a crucial role in the regulation of appetite, glucose homeostasis and body fat. Authors described various clinical and biochemical parameters of obese children aged 6 to 18 years visiting to outpatient department in a tertiary care hospital followed by their correlation with serum leptin levels. It was a prospective observational study.Methods: Obese children with Body Mass Index >2 standard deviation according to WHO chart were included. Endocrinological and syndromic obese childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
1
0
0
Order By: Relevance
“…Children with higher leptin levels had a risk of 11.37 times of obesity. Our results were in line with the study conducted by Gowda et al They reported that in Indian children, serum leptin levels correlate with BMI and all children with obesity had high serum leptin 15 . Zhang et al also found similar results that newly identified children with obesity aged six to 11 years old had higher leptin levels than children without obesity, independent of sex after adjustment for age and Tanner stage, making high leptin levels a predictor of adiposity gain in prepubertal children without obesity 16 …”
Section: Discussionsupporting
confidence: 93%
“…Children with higher leptin levels had a risk of 11.37 times of obesity. Our results were in line with the study conducted by Gowda et al They reported that in Indian children, serum leptin levels correlate with BMI and all children with obesity had high serum leptin 15 . Zhang et al also found similar results that newly identified children with obesity aged six to 11 years old had higher leptin levels than children without obesity, independent of sex after adjustment for age and Tanner stage, making high leptin levels a predictor of adiposity gain in prepubertal children without obesity 16 …”
Section: Discussionsupporting
confidence: 93%